Triethanolamine‐Mediated Magnetically Separable Fe3O4−Pd Nanoparticles Catalyzed Heck Reaction under Ligand‐Free Conditions. Issue 31 (17th August 2021) - Kumar Pal, Chandan; Kumar Jena, Ashis; Das, Dibya; Sahu, Swagatika; Kumar Singh, Rajesh
Abstract: The Fe3 O4 −Pd nanoparticles catalyzed Heck coupling reaction in triethanolamine was performed for the first time in absence of any external ligand. The Fe3 O4 −Pd/triethanolamine/100 °C catalytic system was found to be highly active in achieving good to excellent yields of the desired ( E )‐alkenes. Both acrylates and styrene derivatives were successfully coupled with electron‐rich and electron‐deficient aryl iodides. The scope of the reaction was also expanded to less reactive aryl bromides and aryl chlorides albeit in lower yields. A number of functional groups were well tolerated. More significantly the catalyst showed good recyclability and can be reused up to four consecutive cycles without any decrease in catalytic activity. Abstract : Fe3 O4 −Pd nanoparticles were synthesized in a one‐step hydrothermal method. The magnetically separable Pd nanoparticles were employed as catalyst for the Heck coupling reaction between aryl halidesand olefins. The reaction proceeds under ligand‐free conditions in triethanolamine and resulted good to excellent yield of the products. Further the catalyst were reused up to four consecutive cycles without significant loss in yield.